PSYCHOANALYSIS TOWARDS ANASTASIA STEELE CHARACTER IN FIFTY SHADES DARKER NOVEL - Romiance Pepedek (British (Jurnal Bahasa dan Sastra Inggris), 2018)
This research aims to explain Anastasia’s personality in Fifty Shades Darker novel which is a qualitative analysis and the data source was obtained by reading and note-taking. This research uses Sigmund Freud’s theory which was developed by several experts using the Personality element which consists of Id, Ego, and Super Ego. The results of the research based on the three personality elements Anastasia can be seen from the amount of intention, strong desire to be with Christian Grey even though the pain experienced always haunts her, but her desire to love is stronger than the sense of the pain she experienced. The Anastasia Ego can be known from every way Anastasia did to Christian Gray as if trying to convince the purity of her love for Cristian which Christian was still in doubt even afraid that Anastasia would leave him. Furthermore, Anastasia’s super ego can be known through her independence, she does not want to depend on the wealth of Cristian Gray as her lover and she always gives attention and care for Cristian Gray. Keywords: Personality, Anastasia Stele, Fifty Shades Darker Novel